Comparison of on-line learning algorithms for RBF models in greenhouse environmental control problems - Ferreira, P. M. (2013)
The problem with the adequacy of radial basis function neural networks to model the inside air temperature as a function of the outside air temperature and solar radiation, and the inside relative humidity in an hydroponic greenhouse is addressed.